2004
DOI: 10.1002/jnr.20114
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase and dopamine transporter expression following 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine‐induced neurodegeneration of the mouse nigrostriatal pathway

Abstract: Administration of the neurotoxicant 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) to C57BL/6 mice targets nigrostriatal dopaminergic neurons, leading to cell death and the depletion of striatal dopamine. After MPTP lesioning in young adult mice, surviving nigrostriatal dopaminergic neurons display robust and reproducible return of striatal dopamine weeks to months after injury. Thus, the mouse provides an excellent model with which to investigate the mechanisms underlying neuroplasticity of the nigrostri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 53 publications
(69 reference statements)
9
50
0
Order By: Relevance
“…In addition, exercise had no effect on the time course of dopamine return in MPTPlesioned mice. Specifically, we observed a partial return of striatal dopamine in all MPTP-lesioned mice at day 28 compared with day 5, and this effect was observed to the same degree in exercise and no exercise mice, and in accordance with previous reports (Ricaurte et al, 1986;Bezard et al, 2000;Jakowec et al, 2004). Although HPLC analysis of total tissue catecholamines is an excellent measure of the total dopamine pool, including synaptic, extra-synaptic, vesicular, and cytoplasmic, it may not be an accurate estimate of the amount of dopamine released with activity ( In contrast to total tissue HPLC analysis, using fast-scan cyclic voltammetry in striatal slices of mice exercised for 28 d, we observed an exercise-dependent increase in stimulus-evoked dopamine release in MPTP plus exercise compared with MPTP plus Figure 4.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, exercise had no effect on the time course of dopamine return in MPTPlesioned mice. Specifically, we observed a partial return of striatal dopamine in all MPTP-lesioned mice at day 28 compared with day 5, and this effect was observed to the same degree in exercise and no exercise mice, and in accordance with previous reports (Ricaurte et al, 1986;Bezard et al, 2000;Jakowec et al, 2004). Although HPLC analysis of total tissue catecholamines is an excellent measure of the total dopamine pool, including synaptic, extra-synaptic, vesicular, and cytoplasmic, it may not be an accurate estimate of the amount of dopamine released with activity ( In contrast to total tissue HPLC analysis, using fast-scan cyclic voltammetry in striatal slices of mice exercised for 28 d, we observed an exercise-dependent increase in stimulus-evoked dopamine release in MPTP plus exercise compared with MPTP plus Figure 4.…”
Section: Discussionsupporting
confidence: 93%
“…MPTP (Sigma, St. Louis, MO) was administered in a series of four intraperitoneal injections of 20 mg/kg (free base) at 2 h intervals for a total administration of 80 mg/kg. This regimen leads to ϳ60% loss of nigrostriatal neurons, as determined by unbiased stereological techniques for both TH staining and Nissl substance and an 80 -90% depletion of striatal dopamine levels (Jackson- Lewis et al, 1995;Jakowec et al, 2004). Nigrostriatal cell loss is complete by day 3 after MPTP administration as determined by counting remaining nigrostriatal TH immunoreactive cells and reduced silver staining for degenerating neurons (Jackson-Lewis et al, 1995;Jakowec et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Since the effects of MPTP on pulse acoustics gradually rescinded over the ensuing week after injection, we assume that this was the time course over which MPTP and its metabolites were cleared and neurons recovered normal functioning. However, in mice an 80mgkg -1 dose of MPTP (four injections over eight hours) caused a reduction in striatal dopamine that reached its nadir only after three to seven days (Jakowec et al, 2004). We therefore cannot rule out the possibility that the acute hyperdopaminergic conditions were not subsequently replaced by cell death and hypodopaminergic conditions at some point during the week after injection.…”
Section: Discussionmentioning
confidence: 95%
“…The action of MPTP on the dopamine-producing cells of the SNc in mammals is well established (Jakowec et al, 2004;Smeyne and Jackson-Lewis, 2005). In the brain MPTP is metabolized to 1-methyl-4-phenylpyridinium (MPP+) by the enzyme monoamine oxidase B. MPP+ selectively enters dopamine-producing cells via their dopamine transporter (DAT).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using in vivo brain microdialysis showed that hypoxic ischemia decreases the extracellular dopamine concentration in the striatum of freely moving adult rats (Parrot et al 2003). TH activity is progressively decreased following the loss of dopamine neurons in the striatum as well as in the SN in the hypoxicischemia rodent model (Jakowec et al 2004). Brain damage decreases TH expression in the SN and striatum (Park and Enikolopov 2010).…”
Section: Discussionmentioning
confidence: 98%